Pengaruh Pendidikan Dan Media Sosial Terhadap Akhlak Siswa Dengan Lingkungan Sebagai Variabel Mediasi - Al Irsyad, Daffa Muhammad; Syafi'i, Mohammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
Morality (akhlak) reflects values of morality, ethics, and personality in relationships with God, humans, and the environment. Good morality plays a vital role in shaping noble character, strengthening interpersonal relationships, and creating a harmonious social environment. This study aims to examine the influence of education, social media, and social environment on students' morality. The research employs a quantitative approach with a simple random sampling method, involving 61 students from MI Tarbiyatul Aulad, Cerme, Gresik, as the sample. Research instruments include questionnaires, interviews, observations, and documentation. The findings reveal that, partially, education (p = 0.025) and social media (p = 0.037) have significant effects on students' morality. Simultaneously, education and social media influence morality with an Adjusted R Square value of 0.638. The greatest influence comes from the education variable, with a relationship value of 0.726, while the social media variable has a relationship value of 0.712. Additionally, the social environment significantly mediates the relationship between education, social media, and students' morality. This study provides important implications for developing educational strategies and managing social media to enhance students' morality.